Penerapan Nilai Nilai Pancasila dalam Kehidupan Mahasiswa di Universitas Negeri Surabaya - Nailatul, Ghaziyah; Koes, Mahabillah; Arryant , Radhif; Ika Puspita, Ari Metalin (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The purpose of this study is to investigate how students at Universitas Negeri Surabaya apply the principles of Pancasila in their daily lives. This study focuses on the importance of Pancasila as the foundation of the state and a moral standard in national life. The research employs a qualitative approach to collect data in order to understand the challenges faced by students in implementing the values of Pancasila amid rapid social change and globalization. The results indicate that students have a good understanding of Pancasila, but they still need to improve its implementation in their daily lives, particularly in areas such as transportation. It is hoped that this research will contribute to enhancing character education programs on campus and encourage students to be more active in applying the principles of Pancasila in their lives.